Loss of renal medullary endothelin B receptor function during salt deprivation is regulated by angiotensin II - Kittikulsuth, Wararat (American Physiological Society, 2012)
We have recently demonstrated that chronic infusion of exogenous ANG II, which induces blood pressure elevation, attenuates renal medullary endothelin B (ET(B)) receptor function in rats. Moreover, this was associated with a reduction of ET(B) receptor expression in the renal inner medulla. The aim of this present work was to investigate the effect of a physiological increase in endogenous ANG II (low-salt diet) on the renal ET system, including ET(B) receptor function. We hypothesized that endogenous ANG II reduces renal medullary ET(B) receptor function during low-salt intake. Rats were placed on a low-salt diet (0.01–0.02% NaCl) for 2 wk to allow an increase in endogenous ANG II. In rats on normal-salt chow, the stimulation of renal medullary ET(B) receptor by ET(B) receptor agonist sarafotoxin 6c (S6c) causes an increase in water (3.6 ± 0.4 from baseline vs. 10.5 ± 1.3 μl/min following S6c infusion; P < 0.05) and sodium excretion (0.38 ± 0.06 vs. 1.23 ± 0.17 μmol/min; P < 0.05). The low-salt diet reduced the ET(B)-dependent diuresis (4.5 ± 0.5 vs. 6.1 ± 0.9 μl/min) and natriuresis (0.40 ± 0.11 vs. 0.46 ± 0.12 μmol/min) in response to acute intramedullary infusion of S6c. Chronic treatment with candesartan restored renal medullary ET(B) receptor function; urine flow was 7.1 ± 0.9 vs. 15.9 ± 1.7 μl/min (P < 0.05), and sodium excretion was 0.4 ± 0.1 vs. 1.1 ± 0.1 μmol/min (P < 0.05) before and after intramedullary S6c infusion, respectively. Receptor binding assays determined that the sodium-depleted diet resulted in a similar level of ET(B) receptor binding in renal inner medulla compared with rats on a normal-salt diet. Candesartan reduced renal inner medullary ET(B) receptor binding (1,414 ± 95 vs. 862 ± 50 fmol/mg; P < 0.05). We conclude that endogenous ANG II attenuates renal medullary ET(B) receptor function to conserve sodium during salt deprivation independently of receptor expression.